Kewenangan dan Tanggung Jawab Notaris Terhadap Akta Wasiat yang di Buat Dihadapannya di Kota Padang - Hayaturrahmi, Salma; Fendri, Azmi; Hasbi, M (Universitas Ekasakti, 2023)
A will is a ideed that contains a person's statement about what he wants to happen after he dies, and which can be revoked by him. Notary as a public official is given by laws and regulations the authority to make all agreements and deeds as well as what is desired by those concerned. One of the powers of a notary is to make a deed relating to a will, this is in accordance with the provisions in Article 16 paragraph (1) letter j and k of the Notary Office Law. This study proposes the formulation of the problem, namely: 1 What is the authority of a notary regarding a will made before him in the city of Padang? 2. What are the notary's obligations regarding the will made before him in the city of Padang? 3. What is the form of the Notary's responsibility for the will made before him in the icity of Padang? This research uses a juridical-empirical approach. The results of the research that has been carried out are: 1. The notary's authority over a will made before him in the city of Padang, namely the authority granted by law to a notary is to make a deed related to a will as mandated in UUJN which is related to Article 16 paragraph (1) letter i which reads: